Ozone fumigation effects on the morphology and biomass of Norway spruce (Picea abies L.) saplings - Serafinaviciute B (iForest - Biogeosciences and Forestry, 2009)
The study examined Norway spruce (Picea abies) saplings morphological and biomass sensitivity to ozone fumigation using closed indoor chambers of controlled environment. 4-year-old potted saplings were exposed to three different ozone concentrations: 80 µg/m3, 160 µg/m3, and 240 µg/m3 (7 h/day, 5 days/week). Half of the saplings were harvested after the exposure, and the second half of the saplings were left in the pots in open field until next autumn. The reaction of the saplings of different timing of bud burst was also investigated. The terminal shoot length and the total current year shoot length of Norway spruce saplings after one month of ozone fumigation were significantly (p<0.05) suppressed in all the treatments comparing to the control saplings. The needles of saplings fumigated with ozone were smaller than the needles of control saplings. No significant changes of the biomass of different fractions of Norway spruce saplings were determined right after the fumigation, as well as, in 14 month after the cessation of the fumigation. Norway spruce saplings of early and late timing of bud burst reacted differently to ozone fumigation during the active growth period. The formation of new needles and shoots of the saplings of late bud burst stage was more suppressed comparing to the saplings of the early bud burst stage. The results suggest that the generatively younger organs during their formation are more susceptible to ozone stress. The differences of the needle age between ozone affected and control saplings decreased in one year after the end of fumigation keeping affected Norway spruce saplings in the open field and thus indicating the start of the recovery process.